Endophytic Trichoderma asperellum WNZ-21 produces novel bioactives with anticancer, anti-inflammatory, and hemoprotective properties from fermented bean biomass - Alanazi, Yasmene F.; Alrdahe, Salma Saleh; Moussa, Zeiad; Darwish, Doaa Bahaa Eldin; Alrdahi, Haifa; Saber, WesamEldin I. A. (Frontiers in Microbiology, 2025)
The increasing demand for novel bioactive compounds is driving research into natural sources, particularly through the valorization of agricultural residues. Endophytic fungi have emerged as a promising source of bioactive metabolites with diverse therapeutic potential. We employed a novel approach utilizing the isolated Trichoderma asperellum WNZ-21 [identified morphologically and molecularly (ITS: OR857252, tef1 gene: PP069312)] in semi-solid-state fermentation to bioconvert common bean biomass residue (RCBB) into a rich source of metabolites with significant therapeutic potential. First, T. asperellum efficiently degraded 67.19% RCBB, exhibiting robust enzymatic activity (cellulase: 18.067 units per gram (U/g), xylanase: 15.967 U/g, protease: 5.550 U/g). The fermented RCBB filtrate exhibited a rich chemical profile, including (mg/g RCBB) amino acids (13.51), phenolics (55.22), flavonoids (11.22), tannins (18.90), and several secondary metabolites. FT-IR analysis indicated the presence of a complex mixture of amino acids, polysaccharides, proteins, and other metabolites. GC-MS analysis identified 17 compounds. The fermented biomass possesses multi-biological activities, including anticancer against hepatocellular carcinoma (IC50 = 35.62 μg/mL) and mammary gland breast cancer (IC50 = 59.20 μg/mL) cell lines, with reduced toxicity toward normal human lung fibroblast cells (IC50 = 76.33 μg/mL). It also exhibits anti-hemolytic activity in erythrocyte protection assays, reducing oxidative stress-induced hemolysis to 4.40%. Additionally, the filtrate demonstrates anti-inflammatory activity in a carrageenan-induced paw edema model in rats, providing 36.50% protection after 5 h of treatment. Our findings establish RCBB valorization as a promising route to produce multi-bioactive fungal metabolites. Future research should focus on isolating active compounds, optimizing production, and conducting in vivo studies to fully realize therapeutic potential.